Economic Analysis and Egg Yolk Cholesterol of Local Ducks Fed a Salvinia molesta and Brotia costula Combination - Santoso, Siswanto Imam; Mulyatno, Bambang; Marzuki, Sudiyono; Suprijatna, Edjeng; Setiadi, Agus (Pakistan Journal of Nutrition, 2017)
Background and Objective: Eggs are common foods that are delicious and nutritious, but it had negative aspect of duck eggs that is their cholesterol content. One approach to improving the fat composition of eggs is feed supplementation. The study aimed to evaluate the effects of Salvinia-Brotia (SB) (at various percentages) as a duck feed supplement on the lipid composition (total cholesterol, LDL, HDL and triglyceride levels) of duck eggs. Materials and Methods: The study was carried out according to the guidelines for applied nutrition experiments in poultry. Starter periods of 120 birds 5 week-old Pengging ducks with an average body weight of 734.25±0.52 g were maintained until they were 12 weeks old. The animals were housed in groups under standard conditions in a 20-unit postal cage with 4 individuals/unit. The ducks were fed 3 times/day ad libitum with 2,800 kcal of a metabolic energy and 18% crude protein. Their fattening duration was 49 days. Individuals were chosen for the experiment by a completely randomized design with 4 treatment groups and 6 replicates: T0 (basal diet), T1 (10% SB), T2 (12.5% SB) and T3 (15% SB). Results: SB supplementation in feed for 8 weeks did not significantly affect the body weight or physical characteristics of duck eggs. The addition of 12.5% of SB (T2) lowered the cholesterol compared to the 10% treatment (T1), while this did not differ significantly with the addition of as much as 15% SB (T3). Furthermore, SB supplementation also significantly lowered the LDL content in egg yolks and the provision of 12.5% SB (T2) resulted in the lowest LDL and triglyceride content among the treatments, accompanied by increasing contents of HDL. Utilization of the weed Salvinia molesta and the weed’s waste water Brotia costula as a feed supplement can effectively improve the quality of local duck eggs. Conclusion: The incorporation of 12.5% Salvinia-Brotia (SB) gave the best results in the duck diets would reduce the total cholesterol, feed cost and finally could increase the income over feed cost.